2015
DOI: 10.1007/s12031-014-0488-z
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Functional Role of Reprogramming-Related Long Noncoding RNA (lincRNA-ROR) in Glioma

Abstract: The objective of the study was to investigate the expression and function of reprogramming-related long noncoding RNA (lincRNA-ROR) in glioma and glioma stem cells (GSCs). With real-time quantitative PCR, we analyzed lincRNA-ROR expression levels in 26 primary glioma patients and the expression correlation of lincRNA-ROR with SOX11 and KLF4. To explore its functional role, gain- and loss-of-function studies were performed to assess the effect of lincRNA-ROR on cell proliferation, expression rate of GSCs marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 17 publications
0
72
1
Order By: Relevance
“…In general, lncRNA transcripts exhibit low-level but tissue-specific expression [27] and, with some exceptions [22], their nucleotide sequence is poorly conserved [28]. In the last few years, several studies have shown the importance of lncRNAs to normal physiology as well as to the control of gene expression, wherein they modulate key cellular processes such as cell proliferation, senescence, migration and apoptosis [29,30].…”
Section: The Non-coding Rna Landscapementioning
confidence: 99%
“…In general, lncRNA transcripts exhibit low-level but tissue-specific expression [27] and, with some exceptions [22], their nucleotide sequence is poorly conserved [28]. In the last few years, several studies have shown the importance of lncRNAs to normal physiology as well as to the control of gene expression, wherein they modulate key cellular processes such as cell proliferation, senescence, migration and apoptosis [29,30].…”
Section: The Non-coding Rna Landscapementioning
confidence: 99%
“…1). Mostly, linc-ROR promotes the tumorigenesis, however, it can also be an inhibitor in the proliferation of cancer cells and self-renewal of glioma stem cells (GSCs), partly by blocking KLF4 expression [40].…”
Section: Functional Mechanisms Of Linc-rormentioning
confidence: 99%
“…In tumorigenesis, linc-ROR acts as an oncogene, except for one in glioma [40]. In general, linc-ROR is associated with diverse biological processes including proliferation, differentiation, apoptosis, invasion and metastasis in various human cancers (Table 1).…”
Section: Linc-ror-related Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…lincRNA-RoR modulates reprograming and is indeed expressed at much higher levels in the embryonic stem cell line, H1-hESC, and human-induced pluripotent stem cells than in any other tissue or cell line [36,37]. Knockdown of lincRNA-RoR affects the expression of other stem cell factors such as KLF4, SOX2, and NANOG [38,39], resulting in an exit from the pluripotent state [37]. Together with vlincRNAs [25], HERV-driven lncRNAs can influence the transcriptome of the genes involved in pluripotency.…”
Section: Gene Regulation By Herv-driven Lncrnasmentioning
confidence: 99%